2022
DOI: 10.1111/hir.12442
|View full text |Cite
|
Sign up to set email alerts
|

Community, risk assessment, prevention and control: Black American college students' information seeking on COVID‐19

Abstract: BackgroundDespite the disproportionate impact of the novel coronavirus on Black Americans, there is little research that centres Black college students' information behaviours during the pandemic.ObjectiveThe objective of this study is to identify information needs, resources and use regarding the novel coronavirus pandemic among Black American college students.MethodsThis is a quantitative study among 389 college students in the USA. Data were collected using an online crowdsourced survey instrument. Descript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…Constant accessibility, fluidity, immediacy, timeliness, currency and organization have also emerged as criteria for information source preferences. For example, American college students employed the fluidity of information as a preference criterion when seeking information during the pandemic (Stewart, 2022). Latin and Vietnamese women seeking health information select sources based on their immediacy, thereby avoiding information overload (Hopfer et al, 2021).…”
Section: Context Of Information Source Preferences Researchmentioning
confidence: 99%
“…Constant accessibility, fluidity, immediacy, timeliness, currency and organization have also emerged as criteria for information source preferences. For example, American college students employed the fluidity of information as a preference criterion when seeking information during the pandemic (Stewart, 2022). Latin and Vietnamese women seeking health information select sources based on their immediacy, thereby avoiding information overload (Hopfer et al, 2021).…”
Section: Context Of Information Source Preferences Researchmentioning
confidence: 99%
“…We encountered very few studies, in information science, situated on Black information seeking practices related to the coronavirus. Stewart's 2022 analysis of Black American college students found that health information seeking related to COVID‐19 coalesced around social media and the internet. Symptoms, protective measures, at risk populations and the coronavirus's impact on the Black community were the primary information needs.…”
Section: Introductionmentioning
confidence: 99%
“…Parlak and Baskale (2023) conclude by emphasising the importance of planning interventions to reduce coronavirus anxiety to prevent social media addiction in young people. Stewart (2023) similarly undertook a descriptive survey of student experience, investigating the information needs, resources and use of 389 Black American college students. Unlike Parlak and Baskale (2023), Stewart found no statistically significant gender differences, with one exception: male students believed the internet alone could provide all relevant information about the coronavirus in comparison to female students.…”
mentioning
confidence: 99%
“…Unlike Parlak and Baskale (2023), Stewart found no statistically significant gender differences, with one exception: male students believed the internet alone could provide all relevant information about the coronavirus in comparison to female students. Stewart (2023) notes that educational institutions can play a critical role in information dissemination during crisis events, emphasising the need for critical information literacy skills that intersect with everyday information needs, particularly health literacy.…”
mentioning
confidence: 99%